UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA DALAM PROSES PEMBELAJARAN - Santika Haira; Abdul Rahim; La Ode Sahrin Djalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Self-confidence is a fundamental psychological aspect that significantly influences students' success in the learning process and their personality development. This study aims to examine the efforts of Islamic Religious Education teachers in enhancing students' self-confidence and to analyze the forms of self-confidence that develop during the learning process at SDN 1 Baluara. The research employed a qualitative approach with a case study design. Data were collected through participatory observation of the learning process in Grade IV, in-depth interviews with the Islamic Religious Education teacher and five students, and documentation including learning notes and activity photographs. Data analysis used the Miles, Huberman, and Saldana model through data condensation, data presentation, and conclusion drawing stages. Data validity was tested through source triangulation, method triangulation, and member checking. The findings reveal that teachers implement five main strategies: consistent verbal motivation, varied teaching methods, creation of a safe and supportive learning environment, role modeling in every interaction, and intensive communication with parents. The forms of self-confidence that developed include courage to express opinions, active participation in discussions and presentations, ability to express oneself through various works, positive attitude toward mistakes, and more confident social interactions. This research contributes to achieving SDGs goal 4 on inclusive and participatory quality education, goal 3 on students' mental health and well-being, and goal 10 on reducing inequalities by ensuring every student receives optimal support to develop their self-confidence in Islamic Religious Education learning.